ShORR-1, a Novel Tomato Gene, Confers Enhanced Host Resistance to Oidium neolycopersici - Zhang, Yi; Xu, Kedong; Pei, Dongli; Yu, Deshui; Zhang, Ju; Li, Xiaoli; Chen, Guo; Yang, Hui; Zhou, Wenjie; Li, Chengwei (Frontiers in Plant Science, 2019)
A previous complementary cDNA-amplified fragment length polymorphism (cDNA-AFLP) analysis examined responses to the powdery mildew pathogen Oidium neolycopersici (On) of the resistant cultivar Solanum habrochiates G1.1560, carrying the Ol-1 resistance gene, and susceptible cultivar S. lycopersicum Moneymaker (MM). Among other findings, a differentially expressed transcript-derived fragment (DE-TDF) (M14E72-213) was upregulated in near isogenic line (NIL)-Ol-1, but absent in MM. This DE-TDF showed high homology to a gene of unknown function, which we named ShORR-1 (Solanum habrochaites Oidium Resistance Required-1). However, MM homolog of ShORR-1 (named ShORR-1-M) was still found with 95.26% nucleic acid sequence similarity to ShORR-1 from G1.1560 (named ShORR-1-G); this was because the cut sites of restriction enzymes in the previous complementary cDNA-AFLP analysis was absent in ShORR-1-M and differs at 13 amino acids from ShORR-1-G. Transient expression in onion epidermal cells showed that ShORR-1 is a membrane-localized protein. Virus-induced gene silencing (VIGS) of ShORR-1-G in G1.1560 plants increased susceptibility to On. Furthermore, overexpressing of ShORR-1-G conferred MM with resistance to On, involving extensive hydrogen peroxide accumulation and formation of abnormal haustoria. Knockdown of ShORR-1-M in MM did not affect its susceptibility to On, while overexpressing of ShORR-1-M enhanced MM’s susceptibility to On. We also found that changes in transcript levels of six well-known hormone signaling and defense-related genes are involved in ShORR-1-G-mediated resistance to On. The results indicate that ShORR-1-M and ShORR-1-G have antagonistic effects in tomato responses to On, and that ShORR-1 is essential for Ol-1-mediated resistance in tomato.